RISK PERCEPTION IN PERCEPTION OF BENEFIT, CONVENIENCE, TRUST TO INTEREST USE MOBILE BANKING - Yasmir; Tarjo (Universitas Islam Negeri Alauddin Makassar, 2023)
This research aims to improve the quality of mobile banking services and provide benefits for service users who tend to use technology to fulfill their financial needs, which impacts their interest in using it. Service providers can improve user experience, understand user needs and preferences and develop features and design services that are more intuitive and easy to use. A survey and a purposive sampling strategy with path and simple analysis were used as analytical tools. The study results show that the direct effect of benefits, convenience, trust, and interest has a solid and direct relationship, so the immediate effect is more dominant than the indirect effect involving risk variables. A relatively small indirect effect occurs because the relationship between benefit, ease, trust, risk, and interest is not solid or unclear. The risk variable, namely as a mediator, does not have a substantial effect. The overall risk variable does not significantly mediate the relationship between benefits, convenience, trust, and interest, so the indirect impact will be smaller than the direct effect